The Influence of Ethical Leadership and Organizational Culture on Organizational Commitment with Job Satisfaction as a Mediating Variable at Direktorat Jenderal Pajak (DJP) - Zauki, Imaduddin; Wolor, Christian Wiradendi; Handaru, Agung Wahyu (Cita konsultindo, 2025)
This study aims to examine the influence of Ethical Leadership and Organizational Culture on Organizational Commitment, with Job Satisfaction as a mediating variable, at the Head Office of the Directorate General of Taxes (DJP) in Indonesia. Using a quantitative associative approach, data were collected from 150 functional officers through a Likert-scale questionnaire. The analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results show that Ethical Leadership and Organizational Culture have a positive and significant effect on both Job Satisfaction and Organizational Commitment. Job Satisfaction also has a significant direct effect on Organizational Commitment and serves as a significant mediator in the relationship between Ethical Leadership and Organizational Culture with Organizational Commitment. These findings underscore the critical role of ethical values in leadership and a strong, supportive organizational culture in fostering employee satisfaction and long-term commitment. The implications suggest the importance of leadership development and cultural reinforcement strategies in public institutions to enhance performance and employee engagement.